Analysis of Non-performing Loans Settlement at PT Astra Credit Companies in Review of the Civil Code Article 1313 (Bengkulu City Study) - Ramadhan Nur Ilham; Ana Tasia Pase; Ferawati Royani (Fakultas Hukum Dehasen, 2022)
This study aims to analyze the Non-performing Loans Settlement at PT Astra Credit Companies in Review of the Civil Code Article 1313 (Bengkulu City Study). This study uses the Juridical Empirical approach. This approach aims to understand that the law is not merely a set of statutory rules that are normative in nature, but the law is understood as the behavior of people who are symptomatic in their lives, always interact and relate to social aspects, such as; economic, social and cultural aspects. Any factors that cause non-performing loans at PT Astra Credit Companies should provide legal protection to consumers from a judicial perspective, this is intended if there is a dispute or dispute, legal action can be taken through the courts (litigation) and outside the court (non-litigation) so that consumers or creditors are maintained in terms of security. It is better if the settlement is carried out through mediation so that no one is harmed between the debtor and creditor.